EFFECT OF VEILLONELLA INFANTIUM ON BIOFILM FORMATION OF ORAL STREPTOCOCCUS - RAMADHANI, RATNA; DJAIS, ARIADNA ADISATTYA; BACHTIAR, BOY MUCHLIS (International Journal of Applied Pharmaceutics, 2019)
Objective: Therefore, we aimed in this study to evaluate the effect of Veillonella infantium on the biofilm formation of oral Streptococcus species. Methods: Dual-species biofilm was formed between V. infantium and oral Streptococcus using the wire method, and it was then incubated at 37°C under anaerobic condition for 5 days. Biofilm formation was determined by measuring the DNA concentration. Single species biofilm of oral Streptococcus was generated under the same conditions and was used as a control group. Result: The presence of V. infantium decreased the biofilm formation of Streptococcus mutans, where, in contrast, the formation of biofilm in Streptococcus sanguinis was increased by the presence of V. infantium (p<0.05). Conclusion: The presence of V. infantium decreased the biofilm formation of S. mutans.